Regulation of Advancement and Salary Systems in the Hungarian Public Administration (Academic Journal of Internal Affairs, 2022)
In this study, I examine the advancement and salary systems within the content of the legal relationship. Civil service acts are based on a wide range of personnel policy solutions in the Hungarian public administration. While one act prefers public law and centralized regulatory methods, another tends to focus on labour law and decentralized solutions, while the third seeks to mix them. Thus, in all cases, a similar legislative intention can be identified, yet a completely different approach is reflected behind the regulation of one or another legal relationship. Based on all this, a number of issues can be identified. Which personnel policy system solution is better in line with international trends in civil service legislation? What legal and personnel policy solutions characterize the advancement and remuneration of one or another civil service status? Can differentiation or fragmentation contribute to the modernization of civil service careers? At all, can we talk about solutions in this case or are we currently witnessing some ‘post-bureaucratic’ search for a way?
Keywords: civil service law; civil service career; personnel policy trends; salary systems